THE NOTIONS OF ENGLISH LANGUAGE AND RESEARCH INSTRUCTORS ON THE IMPACT OF DIGITAL TECHNOLOGIES ON THE RESEARCH WRITING PROCESS OF THEIR COLLEGE STUDENTS - Yvonne P. Velasco; Mary Ann V. Dolor (University of Kuningan, 2016)
This is a descriptive study investigating teachers’ view on the impact of digital technologies on the research writing of their students. Using Mishra and Koehler’s (2006) TPCK model as framework, a probe was made on how technology and content are related and how pedagogical strategies in research relates to the use of technology in the classroom. The results reveal that teachers generally viewed the impact of digital technologies as positive but also showed misgivings on some aspects of technology use. The results have significant impact on the ICT policy currently being implemented in most state-run schools in the Philippines.Keywords: digital technologies, teacher perceptions, college research, ICT policy